The Synergy Between Several Bacteria Isolated from the Biodiversity of UB Forest Coffee Litter in Vitro - Gallyndra Fatkhu Dinata; Luqman Qurata Aini; Abdul Latief Abadi (Future Science)
Exploration of bacteria from coffee litter in UB Forest has several new studies, which have the ability as a biocontrol agent. From previous research, it was known the potential of coffee litter bacteria as the single biological control against basal rot in shallots. This study aims to evaluate the ability of bacteria to synergize with other beneficial bacteria of coffee litter. The research consisted of the preparation of coffee litter bacteria isolates and synergy tests using the cross streak method. Based on the research results, not all bacteria can form a consortium. Bacteria that can synergize with each other are Pseudomonas sp., and Alcaligenes faecalis. Three bacteria that cannot be synergized with each other, are Bacillus mycoides, Clostridium sp. and Erwinia sp which produces clear zones up to more than 30 mm. This is preliminary research before starting a bacterial consortium. With this research, it is expected to be a solution for biological control from a consortium of beneficial bacteria from exploration in UB Forest.